Sales representative vs. firm commitment: The moderating role of national distance - Wang, Meng; Gu, Flora F.; Zhao, Danyang; He, Dongjin (Industrial marketing management, 2025)
Although the international relationship marketing literature has extensively studied the subject of commitment, most previous research has investigated commitment at the firm level, with limited attention given to the critical role of the buyer's commitment towards the sales representative (sales-rep) in seller firms. This study, grounded in social exchange theory and international relationship marketing research, investigates how cross-border national distances between exchange dyad influence the effect of firm and sales-rep commitment on both the seller's and the buyer's benefits. Using survey data from international buyers across 29 countries (regions) and secondary national distance indices, we find that the buyer's sales-rep commitment, like firm commitment, positively impacts both the seller's sales share performance and the buyer's special treatment benefits. Furthermore, we find that cross-border economic and cultural distances can weaken the positive effect of firm commitment, while cultural distance strengthens the positive effect of sales-rep commitment. These findings contribute novel insights to social exchange theory by shedding light on the significance of both firm and sales-rep commitment and provide practical recommendations for firms to leverage commitment in managing their international buyers. •This study explores how national distances moderate commitment benefits for sellers and buyers.•It reveals the distinct roles of firm and sales-rep commitment in international business.•Economic distance and cultural distance weaken firm commitment.•Cultural distance strengthens sales-rep commitment.